Although Inconvenient, Baclofen Pumps Do Not Complicate Scoliosis Surgery in Patients With Cerebral Palsy. Issue 8 (15th April 2015) - Yaszay, Burt; Scannell, Brian P.; Bomar, James D.; Sponseller, Paul D.; Shah, Suken A.; Asghar, Jahangir; Samdani, Amer F.; Bastrom, Tracey P.; Newton, Peter O.
Abstract : Study Design: Retrospective review of prospectively collected data. Objective: To compare patients with operative cerebral palsy with and without an intrathecal baclofen pump (ITB) to determine whether an ITB increases the complexity of scoliosis surgery and/or increases the risk of wound complications. Summary of Background Data: Options for baclofen pump placement include before, during, or after scoliosis surgery. There is some concern that prior placement of an ITB and catheter can further complicate cerebral palsy scoliosis surgery and increase the risk for wound complications. Methods: Prospectively collected cases from a multicenter cerebral palsy scoliosis database were reviewed for patients who underwent posterior spinal instrumentation and fusion for a major coronal deformity. These patients were then divided on the basis of whether they had ITB at the time of initial scoliosis surgery. The 2 groups were compared to determine differences in demographics, operative parameters, radiographical outcomes, and rates of wound complications. Results: Of 187 patients identified, 32 had an ITB previously placed (ITB group) and 155 did not (non-ITB group). Both groups were similar in regard to age, sex, Gross Motor Function Classification Scale score, and preoperative Cobb magnitude. When comparing operative parameters, there were no differences in the total operating room time (ITB = 375 ± 127 min, non-ITB = 423 ± 178 min; P = 0.149) or total estimated blood loss (ITB = 2323 ± 1489 mL, non-ITB = 2081 ± 1572 mL; P = 0.424). Postoperatively, the 2 groups had similar correction rates (71% vs . 67%, P = 0.303). As for perioperative wound complications, there were no differences in rates ( P = 0.546) between the ITB (16%) and non-ITB group (15%). Conclusion: Although it may be inconvenient for the surgeon, ITBs do not increase the complexity of surgery or the risk for wound complications. When counseling patients and their caregivers on the timing of pump placement, it does not seem to compromise the care of the patient if the baclofen pump is placed first. Further study is needed to evaluate the safety of pump placement during or after scoliosis surgery. Level of Evidence: 4 Abstract : Although it may be inconvenient for the surgeon, intrathecal baclofen pumps do not increase the complexity of surgery or the risk for wound complications. When counseling patients and caregivers on the timing of pump placement, it does not seem to compromise the care of the patient if the intrathecal baclofen pump is placed first.